Strategi Pondok Pesantren dalam Membentuk Karakter Kepemimpinan pada Santri di Pondok Pesantren Darul Uluum Lumbu Kutowinangun - Puspitasari, Mita; Eliyanto, Eliyanto (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
Islamic Boarding School Strategy in Forming Leadership Character in Santri in Darul Uluum Lumbu Kutowinangun Islamic Boarding School. The research objectives are: (1) to know the steps of forming leadership character in students at Darul Uluum Lumbu Kutowinangun Islamic Boarding School. (2) to know the impact of leadership character building on students at Darul Uluum Lumbu Kutowinangun Islamic Boarding School. This research uses a descriptive qualitative research approach. The informants in this study were caregivers, ustadz/ustadzah, and students. The data collection techniques used are interviews, observation, and documentation. The data analysis techniques used are data reduction, data presentation, and verification/drawing conclusions. The results of this study are: (1) the cultivation of leadership character in students at Darul Uluum Lumbu Kutowinangun Islamic Boarding School is carried out by implementing the creation of organizational environment/culture, direction, habituation, exemplary, and supervision. (2) The impact of cultivating leadership characters on students is the impact personally, the impact on others, the impact on the environment, and the impact on the future.